Veteran Therapeutics: The Promise of Military Medicine and the Possibilities of Disability in the Post‐9/11 United States. (15th July 2020) - Wool, Zoë H.
Abstract: This article draws on a decade of ethnographic work with injured U.S. soldiers and veterans to show the collateral effects of military medicine's salvific promise. In tracing these effects through recent changes in amputation protocols and less spectacular conditions such as posttraumatic stress disorder, I show that the prevalent model of "veteran therapeutics, " which posits cure as the aim of post‐war, has perverse and cruel effects. Drawing on disability theory, I explore alternative ways to read the frictions that soldiers and veterans experience, stretched between the medical model of veteran therapeutics and an emergent sense that cure may be an impossible goal. Alternatively, the article turns to moments when veterans learn to live with disability, rather than living in anticipation of its end. Though small, such moments contain possibilities for a less cruel mode of inhabiting disability, offering incipient signs of what we might call a crip art of failure.